2021
DOI: 10.1002/anie.202101325
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Compounds to Monoaromatics: Selective Cleavage of C−O Bonds over a Brominated Ruthenium Catalyst

Abstract: The cleavage of C−O linkages in aryl ethers in biomass‐derived lignin compounds without hydrogenation of the aromatic rings is a major challenge for the production of sustainable mono‐aromatics. Conventional strategies over the heterogeneous metal catalysts require the addition of homogeneous base additives causing environmental problems. Herein, we propose a heterogeneous Ru/C catalyst modified by Br atoms for the selective direct cleavage of C−O bonds in diphenyl ether without hydrogenation of aromatic rings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 67 publications
(5 reference statements)
2
66
0
Order By: Relevance
“…The inferior synergism of bifunctional catalysis is a common phenomenon for many tandem reactions in biomass conversion. [12,14,[37][38][39] The design of powerful catalysts is extremely important for controlling multiple reactions under a same reaction condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inferior synergism of bifunctional catalysis is a common phenomenon for many tandem reactions in biomass conversion. [12,14,[37][38][39] The design of powerful catalysts is extremely important for controlling multiple reactions under a same reaction condition.…”
Section: Introductionmentioning
confidence: 99%
“…The low proximity of hydrogenation sites and acid sites, and the long‐distance transport of intermediates between different active sites in the abovementioned physical‐mixed or simply assembled tandem catalysts results in unsatisfactory catalytic conversion and selectivity. The inferior synergism of bifunctional catalysis is a common phenomenon for many tandem reactions in biomass conversion [12,14,37–39] . The design of powerful catalysts is extremely important for controlling multiple reactions under a same reaction condition.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, various cross-linking side reactions (predominantly Friedel-Crafts) take place to produce larger fragments, due to the high reactivity of phenolic intermediates and products at high temperatures (Zakzeski et al, 2010). Also, the appropriate design of metal catalysts with enhanced capability to destroy the C-O bonds by hydrogenolysis while inhibiting the hydrogenation of the aromatic rings is highly challenging and in need of solution (Wu et al, 2021). Developing novel strategies like pre-modification of active groups and stabilization of in situ formed active species to obstruct the repolymerization of lignin fragments and the occurrence of over-hydrogenation is essential for comprehensive utilization of lignocellulosic biomass.…”
Section: The Challenges Associated With the Selective C-o Bond Cleava...mentioning
confidence: 99%
“…The three main monomers in lignin have been identified as p-coumaric acid, coniferous alcohol, and mustard alcohol (Jampa et al, 2019). Different monomers are connected by various C-O (e.g., α-O-4, β-O-4 and 4-O-5) and C-C bonds (Figure 1) (Wu et al, 2021). Among these bonds, the β-O-4 bond is dominant (Enright et al, 2019;Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2,9 In the supported metal catalysts, the metals (Pt, Pd, Ru, Ni, Co) usually play a key role in activating hydrogen molecule, which is considered to be necessary in the hydro-processing. [10][11][12][17][18][19][20][21][22][23] However, recently, Huang et al reported that ceria with oxygen vacancies (Ov) can produce H δspecies via the heterolytic pathway and showed good activity in hydrogenation reactions 24 , where the oxygen vacancies played an important role in the formation and stabilisation of hydride species (CeOv 4+ -H -). 25 .…”
Section: Introductionmentioning
confidence: 99%